Comparison of load flow methods on IEEE 9-bus system transmission network using Gauss-Seidel and Newton Raphson / Mohd Syamil Said - Said, Mohd Syamil (2015)
Load flow study is the analysis of a network under steady state operation subjected to inequality constraints in which the system operates. Load flow analysis is the pillar of power system analysis and design. They are necessary for planning, operation, economic scheduling and exchange of power between utilities. The principal information of load flow analysis is to find the magnitude and phase angle of voltage at each bus and the real and reactive power flows in each transmission lines. Therefore, load flow analysis is an importance tool involving numerical analysis applied to a power system. In this analysis, iterative techniques are used because there are no known analytical method to solve the load flow problem. This iterative techniques includes; Gauss-Seidel, Newton Raphson, Decoupled method and Fast Decoupled method. Load flow analysis is difficult and time consuming to perform by hand. The Gauss-Seidel and Newton Raphson methods in detail; Formulation of static load flow equations and computational algorithm is clearly discussed. The objective of this project is to develop a load flow program based on Gauss-Seidel and Newton Raphson methods that will ease the analysis of load flow problem. MATLAB software was used as a programming platform. The program was run on an IEEE 9-bus system test network and the results compared with both methods, i.e. Gauss-Seidel Method and Newton Raphson method.